Aitik mill as hub for a satellite mine: Preliminary development plan of a satellite copper deposit - Markesteijn, M. (author) (2014)
The copper grade in the Aitik mine in northern Sweden is decreasing, therefore other deposits are investigated. One of these deposits is the satellite deposit discussed in this thesis. The grade of this deposit is higher than in Aitik and could thus be used to increase the copper production at the Aitik mine site. The goal of this thesis is to establish a preliminary development plan for a satellite copper deposit, which will be processed at the Aitik processing plant. A literature study showed that the geology of the Aitik mine is the same as that of the satellite mine. Therefore the same design properties could be used as in the Aitik mine. Because of the small surface operation and a steeply dipping ore, the best surface method for the satellite mine is an open-pit operation. The mine design will slightly differ from the Aitik design, the overall slope angle will be higher which results in less waste and thus less extracting costs. The overall slope could be made higher by a smaller bench width. Different cut-off values and elevations of the pit bottom are tried. The best result was obtained with an elevation of the pit bottom of 400 meters. This means that the pit will be 85 meters deep, since the average surface elevation is 485 meters. For the cut-off value is found that the best cut-off value is 55 SEK. This would result in a maximum profit. The fragmentation of the ore could best be done using a finer blasting schedule, instead of using an in-pit crusher. The costs of finer blasting is less than that of an in-pit crusher. The production schedule shows that the surface operation of this satellite mine will be from the $1^{st}$ of January 2018 to the $29^{th}$ of May 2024, this means that the open-pit mine will produce for just under 6,5 years. These dates are hypothetical and depend on the real starting date. After that a underground operation is considered. When this production schedule is used the Net Present Value of the project will be 59,9 MSEK. Therefore this project is economically profitable, ...